Spectrum of Upper Gastrointestinal Endoscopy Findings in Patients with Dyspepsia - Faruque Chowdhury, Md Nahian; Saha, Modhusudhan; Sur Chowdhury, Moloy Kumar (Medicine Today, 2024)
Introduction: This retrospective study was designed to see the endoscopic findings in patients with dyspepsia. Materials and Methods: This was a hospital-based retrospective observational study which included adult patients who underwent upper gastrointestinal endoscopy for dyspepsia from December 2020 to November 2022. Result: Total of 802 patients, male 405 (50.5%) and female 397 (49.5%), age ranging from 14 to 87 years (mean 42.2382 and SD 15.45) were included in this study. Most common abnormal endoscopic finding was non erosive antral gastritis seen in 341 patients (42.5%), followed by pangastritis in 63 (7.86%) and erosive antral gastritis in 52 (6.48%) patients, duodenal ulcer disease including active, with or without outlet obstruction and remission phase 127 (15.82%), gastric ulcer 34 (4.24%) and oesophageal varices 21 (2.62%). In addition, 24 (2.99%), seven (0.87%) and five (0.62%) patients had carcinoma stomach, carcinoma oesophagus and carcinoma duodenum respectively with higher incidence among elderly patients. While, duodenal malignancy and haital hernia were more common in elderly patients, erosive antral gastritis and pangastritis were more common at younger age groups. However, oesophageal varix, duodenal ulcer and antral carcinoma were more common among male patients. Conclusion: Gastritis was the most common endoscopic finding among dyspeptic patients. The incidence of upper GI malignancy was low, but comparatively higher in elderly patients. Medicine Today 2024, Vol.36 (2): 90-94